Corrosion Inhibitory Effects of a New Synthetic Symmetrical Schiff-Base on Mild Steel in Acid Media - Dadgarnezhad, Athareh; Sheikhshoaie, Iran; Baghaei, Fatemeh (Asian Journal of Chemistry, 2016)
In this investigation the inhibitory effect of a new synthesized tetradentate Schiff-base bis(2-hydroxy-1-naphthaldehyde) 1,6-hexadiamine (A1) on the corrosion of mild steel in 1 M HCl and 0.5 M H2SO4 media solutions was studied using various techniques including electrochemical impedance spectroscopy (EIS) polarization curves and weight loss. This compound is a very good inhibitor and has a better behaviour in 1 M HCl than 0.5 H2SO4. A potentiodynarnic polarization study shows this inhibitor has cathodic and anodic nature. Changes in Tafel and impedance parameters Icorr, Rct & Cdl indicate that the absorbed protective film grows with increasing exposure time and concentration of inhibitor. Maximum inhibition efficiency reached was about 97% and 95% at 100 ppm (A1) in 1 M HCl and 0.5 M H2SO4. The adsorption of this inhibitor on mild steel surface in both acidic media follows a Langmuir adsorption isotherm.